Umbilical Cord Blood Saving - A Lifeline for a Lifetime (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Introduction: Umbilical cord blood is blood left over in the placenta and in the umbilical cord after the birth of the baby. Umbilical cord blood saving consists of the collection, processing and cryopreservation of the remaining blood within the umbilicus and placenta following the birth of a child. Within this left over blood, traditionally discarded with the placenta as medical waste, lies a rich source of haematopoietic stem cells same as bone marrow. Cord blood stem cells have advantages over bone marrow in transplants and have been used in more than 30,000 transplants to regenerate healthy blood and immune systems1. Today, stem cell therapies continue to evolve, bringing new hope to patients and their families.Objective: To aware regarding use of stem cells of babys umbilical cord blood in future.Methods: A review of relevant articles and documents and some world standard stem cell banking protocol were undertaken.Conclusion: When these cord blood stem cells are processed and stored, the cells are not only a perfect match for the baby, but it could also provide life saving benefits for siblings and other family members.Bangladesh J Obstet Gynaecol, 2012; Vol. 27(2) : 79-82